Attention Training following Moderate to Severe Traumatic Brain Injury in Adults: A Systematic Review - Soule, Alexa (Department of Psychology, 2024)
Traumatic brain injury (TBI) is a significant contributor to trauma-related mortality and morbidity globally. The high burden of disease for TBI is not only attributable to high incidence rates, but also due to the extensive and often severe post-TBI multi-domain sequelae, of which attentional deficits are particularly prevalent and persistent. Such deficits have far-reaching consequences, given the gateway function of this domain. The high prevalence rate of post-TBI attentional deficits holds true particularly for moderate to severe TBI populations, as more severe injuries are associated with poorer outcomes. Thus exists a clear need from a personal and economic perspective to establish reliable and valid rehabilitation efforts to aid in the recovery of those directly affected by TBI and their families, especially for deficits in attention. The current study aimed to determine the extent and efficacy of attentional training as a form of neuropsychological rehabilitation to ameliorate such deficits following moderate to severe TBI in adults, through a systematic review of relevant literature in this area. Methodology was based on PRISMA guidelines. Databases searched included CINAHL, Cochrane Library, PubMed, PsycINFO, Scopus, and Web of Science. Eligible studies included a combination of RCTs, observational studies and single case designs. All final included studies were assessed for methodological quality and analysed in accordance with the objectives of this review. A total of 7 314 articles were retrieved and of those, 4 845 articles were screened for eligibility. 21 articles met eligibility criteria and were included in this review. Findings of this review suggest that attentional gains can be made in a moderate to severe adult TBI sample, irrespective of time since injury, age, and injury severity. A growing interest in investigating the role that technology (e.g., computerised training) plays in this rehabilitation setting is ever present and needs to be further explored. Further, while findings from this review are suggestive that attentional gains are seen across techniques, it is unclear whether these gains are reflective in the patients' daily life or maintained over time. As such, it is recommended that future research adopts a more holistic assessment approach in which aspects like self-report questionnaires in conjunction with standardised neuropsychological assessments are administered with longer term follow-up assessments. Keywords: attention, cognitive rehabilitation, neuropsychology, TBI